Aqidah in Islamic Teachings: The Foundation of Faith and Its Influence on the Life of a Muslim - Lisanul Hal. A. Panggabean; Khairunisa Aulia Azahwa; Nurjaya; Rosidin (Penerbit Hellow Pustaka, 2025)
This study aims to examine the perfection of Islamic teachings as a divine religion that governs all aspects of human life, as well as the importance of understanding the fundamental framework of Islamic teachings for Muslims, particularly the younger generation and university students. This research employs a qualitative-descriptive approach using the library research method, analyzing primary sources of Islamic teachings, namely the Qur'an, the Sunnah, and ijtihad, along with contemporary Islamic literature. The main findings of this study indicate that Islam is not merely a ritualistic religion but a comprehensive and solution-oriented way of life that addresses various life challenges. However, many Muslims have yet to fully and deeply understand Islamic teachings, often practicing the religion in symbolic or formal ways only. The implication of this research is the need for more structured and in-depth Islamic education to cultivate awareness among Muslims about the importance of comprehensively understanding Islam. Applying the understanding of Islam’s basic framework can help Muslim individuals live consciously and responsibly in accordance with the principles of sharia. The originality of this research lies in its effort to integrate the three primary sources of Islamic teachings as the foundation for a holistic understanding, while also offering a practical approach to introducing the fundamentals of Islam to students and general readers. This study serves as a significant contribution to strengthening religious literacy and understanding Islam as a complete and perfect religion.